2005
DOI: 10.1108/13552550510603298
|View full text |Cite
|
Sign up to set email alerts
|

SMES' internationalization: firms and managerial factors

Abstract: Purpose -To examine the particular organizational and managerial determinants of the different aspects of a firm's export development process: intention, propensity, and intensity. Design/methodology/approach -The study analysed firms' resources and capabilities, managerial characteristics, and managerial attitude and perceptions in a sample of 286 firms in the Spanish wine industry. Statistical analyses using SPSS were carried out to confirm or reject eight hypotheses.Findings -Results confirmed that factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 60 publications
2
90
2
6
Order By: Relevance
“…However, procedural customs, government trade policy, international standards and regulations can also inflict high challenges for realising foreign expansion for SMEs (Suárez-Ortega & Álamo-Vera, 2005). Governmental laws and regulations governing the business activities, such as competition regulation laws antitrust laws, environmental requirements, etc., the aforementioned terms are not ascribable to the external business environment of elements affecting the internationalization process, for they are rather of an administrative nature, i.e.…”
Section: Hypothesis Related To Government Regulation and Internationamentioning
confidence: 99%
See 1 more Smart Citation
“…However, procedural customs, government trade policy, international standards and regulations can also inflict high challenges for realising foreign expansion for SMEs (Suárez-Ortega & Álamo-Vera, 2005). Governmental laws and regulations governing the business activities, such as competition regulation laws antitrust laws, environmental requirements, etc., the aforementioned terms are not ascribable to the external business environment of elements affecting the internationalization process, for they are rather of an administrative nature, i.e.…”
Section: Hypothesis Related To Government Regulation and Internationamentioning
confidence: 99%
“…For small companies intending to internationalise, incentives/motivation factors, endowments, and participation in government schemes and programmes provide needed endorsement and encouragement. However, government trade policy, procedural customs, international standards and regulations as well as low level of bureaucracy can gain competitive advantage and also inflict high challenges for realising foreign expansion for SMEs (Suárez-Ortega & Álamo-Vera, 2005).…”
Section: Managerial and Theoretical Implicationsmentioning
confidence: 99%
“…Generalnie uważa się, że to przede wszystkim bariery wewnętrzne mają negatywny wpływ na podejmowanie internacjonalizacji przez przedsiębiorstwa (Suarez-Ortega & Alamo-Vera, 2005;Cavusgil & Nevin, 1981), a kluczową przeszkodą są czynniki menedżerskie (Kahiya, 2013). Stąd w badaniach przeprowadzonych przez autorów artykułu m.in.…”
Section: Wstępunclassified
“…Suárez-Ortega and Alamo-Vera (2005) investigated the specific organizational and managerial determinants of the various characteristics of a firm's export development process including intention, propensity, and intensity. Their results confirmed that factors impacting export involvement were not the same along the process of export development.…”
Section: Introductionmentioning
confidence: 99%